Voices and Perspectives on International Student Mobility: Where Are Community Colleges? (Comparative & International Education Series, 2021)
Chapter 15|12 pagesEpilogueVoices and Perspectives on International Student Mobility: Where Are Community Colleges?By Krishna Bista, Gregory F. MalveauxThe importance of international education at American community colleges has been increasingly acknowledged in recent years as a foundation. This chapter highlights issues related to international programs and student-faculty expertise and experiences in teaching, as well as study abroad research opportunities at community colleges. These colleges are also rapidly expanding their overseas exchange programs for domestic students to study overseas. Internationalization and international initiatives will remain integral to American community colleges and international students will transcend geographical boundaries to expand their professional fields.